Assessment of Nutritional Status of Children With Congenital Heart Disease: A Comparative Study - Chinawa, Awoere T.; Chinawa, Josephat M.; Duru, Chika Onyinyechi; Chukwu, Bartholomew F.; Obumneme-Anyim, Ijeoma (Frontiers in Nutrition, 2021)
Background: Malnutrition poses a great burden to children in the tropics. However, this seems to be accentuated in children with congenital heart disease. Objectives: The present study is therefore aimed at determining the nutritional status of children with congenital heart disease and compare them with those without congenital heart disease. Methods: This is a cross-sectional study, where congenital heart disease was diagnosed by means of echocardiograph. Anthro software was used to calculate Z scores for weight for age (WAZ), height for age (HAZ), weight for height (WHZ) and body mass index (BMI)-for-age (BAZ). The nutritional status was determined according to WHO classification. Results: It was observed that 38.5% (112/291) of the subjects were wasted compared to 6.25% (16/256) of the controls and the difference was statistically significant (χ2 = 81.2, p<0.001). Stunting was also observed in a greater proportion of subjects than controls as 37.8% (107/291) of subjects were stunted compared with 7.0% (18/256) of the controls (χ2 = 69.9, p<0.001). The under-five subjects had more cases of malnutrition than the controls of same age group. Whereas 42.9% (96/224) of the under-five subjects were wasted, only 6.2% (12/192) the controls were wasted. On the other hand, 4.2% (8/192) of the under-five controls were obese compared to 0.9% (2/224) of the subjects of similar age group. Conclusion Children with congenital heart disease present with varying degrees of malnutrition and is worse compared with children without congenital heart disease. The impact of malnutrition is worse among children under the age of five.